Effectiveness and safety of sacubitril/valsartan in patients with chronic kidney disease: a real-world experience - Couto Pereira, Sara Cristina (2023)
© 2023 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https://creativecommons.org/licenses/by/4.0/).